Ozone Measurements in the Stratosphere from KSR420S-1 and -2 - K. Y. Lee; D. H. Lee; J. Kim; C. J. Park; H. K. Cho (Journal of Astronomy and Space Sciences, 1994)
The Korean sounding rockets(KSR420S-1, -2) equipped with ozone detectors have been launched at An-heung, Chungchungnam-do, on June 4 and September 1, 1993, respectively. The ozone detector is used to measure the attenuation of solar UV radiation for various frequency bands in the stratosphere, to obtain vertical profiles of the ozone number density in the stratosphere. They confirm that the maximum ozone densities occur near 25km, which is quite consistent with the mean value in the mid-latitude region. Our results from KSR420S-1 and -2 are compared with the other observational data from the Dobson spectrophotometer at Yonsei Univ., the LIDAR at Kyunghee Univ., the SBUV from Nimbus satellite, and the TOVS from NOAA satellite, which were performed simultaneously with the sounding rocket experiment.